Implementation of the Culturally Independent Village Policy in Katongan Village, Nglipar Subdistrict, Gunung Kidul Regency - Ahmad Rizaldi Rusdi; Minardi Minardi (JGov: Journal of Governmentality, 2026)
This research was conducted to examine in-depth the implementation of the Independent Cultural Village policy in Katongan Village, Nglipar Subdistrict, Gunungkidul Regency, Yogyakarta Special Region Province. The primary focus of the research was three key aspects: how the village government develops local potential, the extent of community participation in the policy process, and the village government's ability as policymakers to implement and direct the program. The research method used was descriptive qualitative. Data were obtained through observation, in-depth interviews with various key informants, and documentation studies related to policy implementation. All collected data were analyzed using an interactive approach involving data reduction, data presentation, and systematic conclusion drawing. The results indicate that the implementation of the Independent Cultural Village policy in Katongan has been relatively successful. This relates to the development of village potential, which is focused on four main pillars: cultural villages, tourism villages, entrepreneurial villages, and prime villages. Although the development of these potentials is not a new, widely recognized initiative, it rather strengthens existing ones. Community participation has been quite active during the implementation phase, such as involvement in arts programs, tourism, and local businesses. However, community participation remains limited to the planning and evaluation stages, resulting in community aspirations not being fully addressed. Meanwhile, village governments have demonstrated their ability to manage programs through targeted strategies and target setting to promote village independence. However, disagreements persist between village governments and the community regarding the use of special funds.